Sustainable Marketing in the Digital Age: A Systematic Review of the Latest Strategies and Tactics - Widiastuti, Erni; Sukesi, Sukesi; Sarsiti, Sarsiti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This literature review describes the latest developments in the field of Sustainable Marketing in the Digital Age, focusing on a systematic review of the latest strategies and tactics used by companies in meeting the demands of consumers who are increasingly aware of environmental and social issues. In an ever-evolving digital age, sustainable marketing has become essential in achieving sustainable business goals, while still considering the positive impact on society and the environment. This study analyzes the use of digital technology in sustainable marketing, with an emphasis on the use of social media and digital platforms to educate and interact with consumers about sustainability issues. The integration of sustainable values in marketing strategy is also in the spotlight, illustrating how companies apply sustainable principles throughout the life cycle of products and business processes. In addition, this study discusses the importance of big data analysis in sustainable marketing decision making, as well as the role of consumer engagement through interactive content and participation in sustainable initiatives. The results of this literature review provide important insights for marketing practitioners, business managers, and researchers in understanding the latest trends and leveraging them to create effective sustainable marketing practices in the ever-evolving digital age. Keywords: Sustainable Marketing, Digital Age, Big Data Analysis